2015
DOI: 10.1002/trtr.1387
|View full text |Cite
|
Sign up to set email alerts
|

Early Literacy Research

Abstract: This article shares recent research findings in early literacy that every primary grade teacher has had questions about at one time or another ranging from handwriting to phonemic awareness, writing to concepts about print, and more. The article reports research that elaborates upon and extends early literacy research that was reported by the National Early Literacy Panel Report in 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Research, mostly on an international level, has explored the views of teachers of preprimary and early primary school (first-grade) regarding the teaching of language (Cook, 2012;Guo, Piasta, Justice, & Kaderavek, 2010;Hawken, Johnston, & McDonnell, 2005;Hindman & Wasik, 2008;Kimmy, 2017;Lynch, 2009;Maloch, Flint, Eldridge, Harmon, Loven, Fine, & Martinez, 2003;Õun, Ugaste, Tuul, & Niglas, 2010;Reutzel, 2015;Sak, Tantekin-Erden, & Morrison, 2016;Sandvik, van Daal, & Ader, 2013;Shaughnessy & Sanger, 2005). In Greece, research focusing on the study of curricula and the perceptions of first-grade primary school teachers of their teaching approaches for language and pre-primary school teachers for literacy hardly exists (Stellakis, 2012;Tafa, Manolitsis, & Fasoulaki, 2011).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Research, mostly on an international level, has explored the views of teachers of preprimary and early primary school (first-grade) regarding the teaching of language (Cook, 2012;Guo, Piasta, Justice, & Kaderavek, 2010;Hawken, Johnston, & McDonnell, 2005;Hindman & Wasik, 2008;Kimmy, 2017;Lynch, 2009;Maloch, Flint, Eldridge, Harmon, Loven, Fine, & Martinez, 2003;Õun, Ugaste, Tuul, & Niglas, 2010;Reutzel, 2015;Sak, Tantekin-Erden, & Morrison, 2016;Sandvik, van Daal, & Ader, 2013;Shaughnessy & Sanger, 2005). In Greece, research focusing on the study of curricula and the perceptions of first-grade primary school teachers of their teaching approaches for language and pre-primary school teachers for literacy hardly exists (Stellakis, 2012;Tafa, Manolitsis, & Fasoulaki, 2011).…”
Section: The Current Studymentioning
confidence: 99%
“…al., 2003;Morris, 2015;Õun et. al., 2010;Pearson et al, 2007;Pianta et al, 1999;Reutzel, 2015;Rimm-Kaufman & Pianta, 2000;Sak et. al., 2016;Sandvik et al, 2013;Shaughnessy & Sanger, 2005;Torres, 2009;Xefteri, 2017;Xue & Meisels, 2004) and data from UNESCO (UIL, 2010(UIL, , 2017(UIL, , 2018UNESCO, 2005UNESCO, , 2007UNESCO, , 2015UNESCO, , 2017.…”
Section: Findings' Correlation With International Research Datamentioning
confidence: 99%
“…Such instruction need not and should not consume the literacy block. We adapted Reutzel's (2015) 12-minute lesson aimed at building phonological awareness and letter recognition. Here, the lesson was adapted to support student autonomy by embedding opportunities for students to make what Cambria and Guthrie (2010) called mini-choices.…”
Section: Phonological Awareness and Alphabet Knowledge Go Hand In Handmentioning
confidence: 99%
“…Research has indicated that the teaching of print concepts supports emergent readers' developing proficiencies (Reutzel, 2015). The NELP report included concepts of print among the secondary early skills found to correlate with either later decoding or later comprehension (Shanahan & Lonigan, 2013).…”
Section: Emergent Readers Need To Develop Strong Print Awarenessmentioning
confidence: 99%
“…Still other students are introduced to letters at a slow pace, disconnected from continuous text with few opportunities for practical application, and may forget the letters learned weeks ago. As Reutzel (2015) asserted, It turns out that teaching alphabet knowledge to young children, something that ostensibly seems easy to teach in the minds of many laypersons and even other K-12 educators, is actually quite a complex, abstract task for young children to achieve. (p. 16) Indeed, we know far less about which particular teaching strategies are most effective in building students' letter knowledge, but we do know that contrived scripts and fixed instructional sequences inhibit letter-learning efficiency (McKay & Teale, 2015).…”
Section: Emergence Of Letter Knowledgementioning
confidence: 99%